ASSOCIATION BETWEEN DIABETES MELLITUS AND FROZEN SHOULDER: A CROSS-SECTIONAL STUDY. - Sandhiya1 , Uswa Ali Qazi2 , Sadhna Bai3 , Haresh Kumar4 , Safdar Ali Pervaiz Tunio5 , Jaendo Khan Daiedano6 . (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2023)
ABSTRACT: BACKGROUND: Adhesive capsulitis, another name for frozen shoulder, is a painful disease that limits the degree of movement in the joint that connects the shoulders. OBJECTIVE: The aim of this cross-sectional study was to investigate the association between diabetes mellitus (DM) and frozen shoulder syndrome (FSS). METHODS: A grand total of 300 volunteers, which includes those who have or do not have diabetes mellitus, were chosen from the local population. To ascertain whether FSS was present, an extensive medical assessment was performed on each individual. The clinical standards, like those defining symptoms and signs of discomfort & limited shoulder mobility, were used to make the diagnosis of FSS. Every participant’s socioeconomic status, medical records, and relevant clinical details were gathered. RESULTS: The study had 300 people, 150 of whom had diabetic mellitus (DM) and 150 of whom did not. The participants’ average ages ranged from 55 to 10.2 years, with a mean age of 55. 60% of individuals lacked DM, while 70% of participants with DM were female. Individuals with DM were shown to have a considerably higher incidence of frozen shoulder than those without DM. Frozen shoulder was identified in 45% (n=67) of people with DM, but only in 20% (n=30) of persons without DM. Between the two groups, there was a statistically significant difference in prevalence (p 0.05). CONCLUSION: The present cross-sectional research offers proof that DM & FSS are significantly related. It was discovered that individuals having DM had a greater chance of acquiring FSS than people with no DM. These results emphasize the need of addressing shoulder symptoms in DM individuals, since early diagnosis and treatment may help stop the beginning or worsening of FSS. In order to comprehend the fundamental mechanisms & causation of this link, more long-term research is required